Unusual Clinical Presentation of Clear Cell Sarcoma Masquerading as Cutaneous Lymphoma, in a Young Male - Dhal, Ipsita; Mishrikotkar, Soumya; Pal, Paramita Rudra (Asian Pacific Journal of Cancer Biology, 2024)
Background: Clear cell sarcoma of soft tissue is an exceedingly rare tumor that originates from the neural crest cells. These tumors are histologically characterized by the presence of clear cells that contain accumulated glycogen. Clear cell sarcomas share histological and immunohistochemical features with malignant melanoma. They commonly arise from tendinous sheaths and aponeuroses, with the lower limbs, particularly around the ankles, being the most common site. Tumors arising in the upper extremities are rare, and very few primary clear cell sarcoma cases have been described in the chest wall and scapular soft tissues. They usually present as a solitary mass. Materials and Methods: Here we are reporting a case of clear cell sarcoma in a young boy, presenting with multifocal lesions involving the trunk, both upper and lower extremities, lymph nodes, bone marrow, and many internal viscera. Results: The case described an unusual presentation of clear cell sarcoma with multifocal involvement, which is rare compared to the typical presentation as a solitary mass. Conclusion: The reported case demonstrates a very unusual presentation of clear cell sarcoma involving multiple sites, highlighting the importance of considering a wide differential diagnosis when encountering multifocal soft tissue lesions.